Surveillance and Genomics of Toxigenic Vibrio cholerae O1 From Fish, Phytoplankton and Water in Lake Victoria, Tanzania - Hounmanou, Yaovi M. Gildas; Leekitcharoenphon, Pimlapas; Hendriksen, Rene S.; Dougnon, Tamegnon V.; Mdegela, Robinson H.; Olsen, John E.; Dalsgaard, Anders (Frontiers in Microbiology, 2019)
The occurrence of toxigenic Vibrio cholerae O1 during a non- outbreak period in Lake Victoria was studied and genetic characteristics for environmental persistence and relatedness to pandemic strains were assessed. We analyzed 360 samples of carps, phytoplankton and water collected in 2017 during dry and rainy seasons in the Tanzanian basin of Lake Victoria. Samples were tested using PCR (ompW and ctxA) with DNA extracted from bacterial isolates and samples enriched in alkaline peptone water. Isolates were screened with polyvalent antiserum O1 followed by antimicrobial susceptibility testing. Whole genome sequencing and bioinformatics tools were employed to investigate the genomic characteristics of the isolates. More V. cholerae positive samples were recovered by PCR when DNA was obtained from enriched samples than from isolates (69.0% vs. 21.3%, p < 0.05), irrespectively of season. We identified ten V. cholerae O1 among 22 ctxA-positive isolates. Further studies are needed to serotype the remaining ctxA-positive non-O1 strains. Sequenced strains belonged to El Tor atypical biotype of V. cholerae O1 of MLST ST69 harboring the seventh pandemic gene. Major virulence genes, ctxA, ctxB, zot, ace, tcpA, hlyA, rtxA, ompU, toxR, T6SS, alsD, makA and pathogenicity islands VPI-1, VPI-2, VSP-1, and VSP-2 were found in all strains. The strains contained Vibrio polysaccharide biosynthesis enzymes, the mshA gene and two-component response regulator proteins involved in stress response and autoinducers for quorum sensing and biofilm formation. They carried the SXT integrative conjugative element with phenotypic and genotypic resistance to aminoglycoside, sulfamethoxazole, trimethoprim, phenicol, and quinolones. Strains contained a multidrug efflux pump component and were resistant to toxic compounds with copper homeostasis and cobalt-zinc-cadmium resistance proteins. The environmental strains belonged to the third wave of the seventh pandemic and most are genetically closely related to recent outbreak strains from Tanzania, Kenya, and Uganda with as low as three SNPs difference. Some strains have persisted longer in the environment and were more related to older outbreak strains in the region. V. cholerae O1 of outbreak potential seem to persist in Lake Victoria through interactions with fish and phytoplankton supported by the optimum water parameters and intrinsic genetic features enhancing survival in the aquatic environment.